(3GdJShjb GdeUQaj s - (3eMeO Ndjd(B, (3GdcShGfjs ((3YeGf(B:s (3OGQ GdGHJcGQ ddfTQ hGdJhRjY(B,s, 2023)
(3jbOe cJGH (B"(3GdJShjb GdeUQaj(B" (3OQGSI eJYebI dYGde GdJShjb aj GdbWGY GdeUQaj(B. (3jHOC GdcJGH HJbOje eaGgje CSGSjI Mhd GdJShjb HTcd YGe hcjajI JWHjbg aj GdbWGY GdeUQaj(B. (3Ke jfJbd Edi efGbTI OhQ GdJShjb GdEdcJQhfj aj JYRjR GdbOQI GdJfGaSjI ddeUGQa, MjK jSJYQV CMOK GdJbfjGJ hGdGJLGgGJ aj gPG GdeLGd(B. (3jJfGhd GdaUd GdKGdK CgejI GdJShjb OGNd GdeDSSI GdeUQajI hcja jecf Cf JSGge GdEOGQI GdaYGdI ddJShjb aj JMbjb CgOGa GdHfc(B. (3hCNjkQG, jHMK GdaUd GdQGHY aj SjGSGJ GdJSYjQ GdeUQaj hYdGbJgG HGdGSJQGJjLjGJ GdJShjbjI(B. (3jYJHQ gPG GdcJGH eQLkYG bjkeG ddeNJUjf aj eLGd GdJShjb GdeUQaj, MjK jhaQ dge QDi bjeI Mhd GdJMOjGJ hGdaQU GdJj JhGLg gPG GdbWGY(B.s
(3GdeQGLY U(B.267s
Keywords: (3GdJShjb (B- (3GdHfhc s; (3GdJShjb GdeUQajs